2018
DOI: 10.1002/jcp.27654
|View full text |Cite
|
Sign up to set email alerts
|

WISP1 silencing confers protection against epithelial–mesenchymal transition of renal tubular epithelial cells in rats via inactivation of the wnt/β‐catenin signaling pathway in uremia

Abstract: Uremia can affect hepatic metabolism of drugs by regulating the clearance of drugs, but it has not been clarified whether gene silencing could modulate the epithelial–mesenchymal transition (EMT) process in uremia. Hence, we investigated the effect of WISP1 gene silencing on the renal tubular EMT in uremia through the wnt/β‐catenin signaling pathway. Initially, microarray‐based gene expression profiling of uremia was used to identify differentially expressed genes. Following the establishment of uremia rat mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
(72 reference statements)
0
14
0
Order By: Relevance
“…Our findings are just one example of how the matricellular protein WISP1 alters cellular fate and differentiation decisions. Past studies have implicated WISP1 in the balance of osteoblast versus adipocyte formation (38,39) and, more broadly, epithelial cells adopting a mesenchymal cell fate (epithelial-mesenchymal transition) (40)(41)(42)(43). As CCN family members, including WISP1, have numerous extracellular binding partners it is understandable that they may have context-dependent effects on cellular differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are just one example of how the matricellular protein WISP1 alters cellular fate and differentiation decisions. Past studies have implicated WISP1 in the balance of osteoblast versus adipocyte formation (38,39) and, more broadly, epithelial cells adopting a mesenchymal cell fate (epithelial-mesenchymal transition) (40)(41)(42)(43). As CCN family members, including WISP1, have numerous extracellular binding partners it is understandable that they may have context-dependent effects on cellular differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…9A), indicating that the transition of fibroblasts into myofibroblasts was also the important mechanism of LF fibrosis. It has been reported that CCN protein induces a-SMA expression in the fibrosis of many organs (Chen et al, 2019;Morales et al, 2011). Therefore, we suspected that WISP-1 might also induce a-SMA expression in LF fibroblast during fibrogenesis.…”
Section: Wisp-1 Promotesa-sma Expression Through Hedgehog Signalingmentioning
confidence: 87%
“…CircRNAs are competitive endogenous RNAs (ceRNAs) that regulate gene expression by sponging their target miRNAs [ 30 32 ]. For example, circular RNA YAP1 protects against ischemic injury by regulating the miRNA-21-5p/PI3K/AKT/mTOR axis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%